INDEKS KUNING TELUR (IKT) DAN HAUGH UNIT (HU) TELUR PUYUH (Coturnix coturnix japonica) SETELAH PENAMBAHAN TEPUNG KUNYIT (Curcuma longa L.) DAN TEPUNG IKAN PADA PAKAN - Suparyanti S; Koen Praseno; Tyas Rini Saraswati (Jurnal Akademika Biologi, 2013)
This researchwasdesigned to study the potential of turmeric powder and fish powder in the feed to improve of Yolk Index (YI) and Haugh Unit (HU) of Coturnix coturnix japonica. Quail tread with turmenic powder 54 mg/quail/day with protein 25,19%. The parameters include daily feed, yolk indek (YI) and haugh unit (HU).. Experimental animal used in this study were 60 female japanese quails, which were divided into 4 experimental group each treatment 3 quails with 5 replication, while parameters measurement was carried out for 4 months, namely P0 (standard feeding), P1 (85% standard feeding and 15% fish powder feeding), P2 (85% standard feeding and 15% fish powder feeding added with turmeric powder on age 2 to 120 weeks), P3 (85% standard feeding and 15% fish powder feeding added with turmeric powder on age 45-75 days), The data obtained was analyzed using Analysis of Variance (Anova) on the basis of a completely randomized design (CRD) followed by duncan test with a 95% confidence interval overall analysis was using the sotwere SAA 9,1 for windows. The results showed that the addition of turmeric powder with concentration of 54 mg/quail/day and fish powder on feed didn’t affect the yolk index and haugh unit. The addition of turmeric powder (Curcuma longa L.) and fish powder in this study had no potential to increase the yolk index and haugh unit of quail’s egg (Coturnix coturnix japonica). Key words: Yolk Index (YI), Haugh Unit (HU),fish powder, quail (Coturnix coturnix japonica),  turmeric powder